Avaliação da influência da terapia fotodinâmica antimicrobiana na alteração de cor da estrutura dentária e de uma resina composta - Lorenzetti, Camila Cruz [UNESP] (2015)
This study, divided in two studies, was to evaluate: (1) the influence of antimicrobial photodynamic therapy in color change dentin using methylene blue and curcumin as photosensitizers in concentrations of 20, 40 and 60 uM and pre irradiation times 2 to 5 minutes, irradiated with a LED light source; and (2) the effect of the same antimicrobial treatment with the same photosensitizers, concentrations and pre-irradiation times used in the previous study, but on color change in a microhybrid composite. In the first study were produced 130 specimens from extracted human teeth, which were cut in Isomet cuts machine. After immersion in the photosensitizers, the color changes were evaluated using a spectrophotometer colorimeter in four stages: before the immersion in solutions of photosensitizers (L0) after immersion in photosensitizers (L1) after irradiation (L2), after 10 days (L3) after 30 days (L4) and 60 days (L5). There was a high variation of ΔE averages of the methylene blue groups independently of the concentration and exposure time, decreasing from a reading of 10 days. With curcumin groups, there was no significant difference initial variation control, remaining next to it in the subsequent readings. Both photosensitizers showed clinically significant changes in dentin according to the classification of ―National Bureau of Standards‖ (NBS), with a lowest change to curcumin that of methylene blue. In the second study were made 130 specimens microhybrid composite resin (Filtek Z250XT) using a steel matrix (10x2mm). After preparation of the specimens, they were immersed in solutions of photosensitizers and subsequently evaluated with a spectrophotometer Colorimetry in the same color reading moments performed in the previous study (initial, after immersion, after light irradiation, after 10, 30 and 60 days). In methylene blue groups was no statistically significant difference... (Complete abstract access below)